Role of Creative Economy on Local Economic Development - Satrio Pratomo; Khusnul Ashar; Dias Satria (Journal of Indonesian Applied Economics, 2021)
Local economic development in Indonesia is still quite minimal, requiring new policies and strategies such as the creative economy. This study analyzes the influence of the creative economy as represented by the concentration of the creative class and its supporting factors on local economic development. Using panel data from Barekraf / BPS statistics for 2011-2015, the results show that the concentration of the creative working class has a significant impact on local economic development including supporting factor such as proportion graduated high educated, electrification ratio and internet coverage ratio. These findings indicate that the creative working class can encourage the growth of local economic development in a region.